The Effect of Increasing Dialysate Magnesium on Serum Calcification Propensity in Subjects with End Stage Kidney Disease: A Randomized, Controlled Clinical Trial - Bressendorff, Iain; Hansen, Ditte; Schou, Morten; Pasch, Andreas; Brandi, Lisbet (Clinical journal of the American Society of Nephrology, 2018)
Serum calcification propensity is a novel functional test that quantifies the functionality of the humeral system of calcification control. Serum calcification propensity is measured by T , the time taken to convert from primary to secondary calciprotein particle in the serum. Lower T represents higher calcification propensity and is associated with higher risk of cardiovascular events and death in patients with ESKD. Increasing magnesium in serum increases T , but so far, no clinical trials have investigated whether increasing serum magnesium increases serum calcification propensity in subjects with ESKD. We conducted a single-center, randomized, double-blinded, parallel group, controlled clinical trial, in which we examined the effect of increasing dialysate magnesium from 1.0 to 2.0 mEq/L for 28 days compared with maintaining dialysate magnesium at 1.0 mEq/L on T in subjects undergoing hemodialysis for ESKD. The primary end point was the value of T at the end of the intervention. Fifty-nine subjects were enrolled in the trial, and of these, 57 completed the intervention and were analyzed for the primary outcome. In the standard dialysate magnesium group, T was 233±81 minutes (mean±SD) at baseline (mean of days -7 and 0) and 229±93 minutes at follow-up (mean of days 21 and 28), whereas in the high dialysate magnesium group, T was 247±69 minutes at baseline and 302±66 minutes at follow-up. The difference in T between the two groups at follow-up (primary analysis) was 73 minutes (between-group difference; 95% confidence interval, 30 to 116; <0.001), and the between-group difference in serum magnesium was 0.88 mg/dl (95% confidence interval, 0.66 to 1.10; =0.001). Increasing dialysate magnesium increases T and hence, decreases calcification propensity in subjects undergoing maintenance hemodialysis. This article contains a podcast at https://www.asn-online.org/media/podcast/CJASN/2018_08_21_CJASNPodcast_18_9_B.mp3.